2020
DOI: 10.36941/jesr-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Application of MMPI-2 and OQ-45 to Detect and Measure the Effectiveness of Psychological University Counselling

Abstract: The main aim of the present study concerns the analysis of the evolution of psychological distress during university counselling treatment, taking into account the initial mental health conditions of the students involved by means of standardized clinical measures. During a preliminary interview, we collected socio-demographic information, academic problems and health conditions of 110 university students who had requested psychological counselling. We applied the MMPI-2 questionnaire prior to the treatment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“… Biasi et al (2020) examining the role that certain personality traits measured at the pre-test exerted on the efficacy of counseling intervention, found that the Pychopathic Deviate dimension of the MMPI-2 predicted better outcomes. In addition to the findings of Biasi et al (2020) , in our study, no personality traits among Negative Affectivity, Detachment, Antagonism, Disinhibition, and Psychoticism, measured through the PID-5 BF at the pre-test, were related to outcome. As argued by Thalmayer (2018) , it seems logical to assume that personality is associated with intervention outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… Biasi et al (2020) examining the role that certain personality traits measured at the pre-test exerted on the efficacy of counseling intervention, found that the Pychopathic Deviate dimension of the MMPI-2 predicted better outcomes. In addition to the findings of Biasi et al (2020) , in our study, no personality traits among Negative Affectivity, Detachment, Antagonism, Disinhibition, and Psychoticism, measured through the PID-5 BF at the pre-test, were related to outcome. As argued by Thalmayer (2018) , it seems logical to assume that personality is associated with intervention outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A possible origin of university students’ distress may be difficulties associated with the specific developmental stage of emerging adulthood ( Riva Crugnola, 2017 ). Several developmental challenges associated with this life stage, including separation from the family, the establishment of new social relationships, long-term goal setting, and financial management can, in fact, contribute to the onset of anxiety, depression, and general psychological distress ( Ghilardi et al, 2018 ; Biasi et al, 2020 ). The demand for psychological support from college students is increasing worldwide ( Center for Collegiate Mental Health, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first is the dissatisfaction of the treatment given by the traditional approaches as a criticism for the process of mental health therapy (Worell & Remer, 2003;Evans, et al 2005). Second, the mental health must consider the sex, gender and cultural differences in terms of prevalence, etiology, diagnose and therapy action (Biasi, et.al. 2020;Pratikta, 2020).…”
Section: Discussionmentioning
confidence: 99%